Utility of 5-ALA for resection of CNS tumours other than high-grade gliomas: a protocol for a systematic review - Michael D Jenkinson; Ashwin Venkatesh; Colin Watts; Michael T C Poon; Victoria Wykes; Stephen John Price; Puneet Plaha; Georgios Solomou; Melissa Gough; Conor S Gillespie; Aref-Ali Gharooni; Waqqas Patel (BMJ Open)
Introduction 5-aminolevulinic acid (5-ALA) is a proagent developed for fluorescent-guided surgery for high-grade glioma patients associated with a significant increase in resection conferring survival. 5-ALA was shown to penetrate the blood–brain barrier accumulating in malignant glioma cells with high selectivity, sensitivity and positive predictive value. However, those have yet to be explored aiding diagnosis for tumours of the central nervous system (CNS) other than high-grade gliomas (HGG). No up-to-date systematic review exists reporting the major surgical outcomes and diagnostic accuracy. We sought to conduct a systematic review of the literature summarising surgical outcomes, evaluate the quality of diagnostic accuracy reported in the literature and qualitatively assess the evidence to inform future studies.Methods and analysis We will search electronic databases (Medline, Embase) with subsequent interrogation of references lists of articles reporting the use of 5-ALA for brain tumours other than high-grade glioma adult patients, which also report the extent of resection and/or survival. Prospective and retrospective cohort and case–control studies with more than five patients will be included. Two independent reviewers will screen the abstracts and full articles, with a third reviewer resolving any conflicts. The data will be extracted in a standardised template and outcomes will be reported using descriptive statists. The quality of non-randomised studies will be appraised.Ethics and dissemination The study will summarise the available evidence on the effect of the clinical utility of 5-ALA in achieving resection and improving survival and its diagnostic accuracy for tumours of the CNS other than HGG. The data will be presented nationally and internationally and the manuscript will be published in a peer-reviewed journal. No ethical approvals were needed. The aim is to inform prospective studies minimising reporting bias allowing for more reliable, reproducible and generalisable results. The study has been registered in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines.PROSPERO registration numberCRD42021260542.